1970
DOI: 10.1002/cber.19701030529
|View full text |Cite
|
Sign up to set email alerts
|

Phosphororganische Verbindungen, 64: Allyl‐Propenyl‐Umlagerungen Das elektrochemische Verhalten einiger Propenylverbindungen

Abstract: Allyl-aryl-sulfone, Allyl-diphenyl-phosphinoxid, Allylphosphonsiiure-diathylester, Allyltriphenyl-phosphoniumbromid und Allyl-triphenyl-arsoniumbromid lagern sich an basischem A1203 in die entsprechenden I-Propenyl-Verbindungen um. Allyl-diphenyl-phosphin und Diallyl-phenyl-phosphin isomerisieren sich unter Mitwirkung von Natriumathylat zu den cntsprechenden 1 -Propenyl-Verbindungen. Die Allyl-und 1 -Propenyl-Verbindungen werden IR-und NMR-spektroskopisch sowie polarographisch charakterisiert. -Bei der kathodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As far as the literature data is concerned, basic catalysts have been used for the isomerization of O ‐allyl ethers, but not for the isomerization of O ‐allyl acetals and O ‐allyl esters. The following allyl ethers, among the examined in this work, were isomerized in the presence of basis catalytic systems: 2 ( Q = t ‐BuO, t ‐BuOK), 3 (PhCH 2 , t ‐BuOK), 4 ( neo ‐menthyl O , LDA or t ‐BuOK), 6 (PhO, t ‐BuOK or LDA, or Vercade's super‐base,), 7 ( t ‐BuOK), 8 ( t ‐BuOK), and 9 ( t ‐BuOK). As mentioned above, the catalytic systems crown ether‐base type have not been applied to the O ‐allyl compounds isomerization so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the literature data is concerned, basic catalysts have been used for the isomerization of O ‐allyl ethers, but not for the isomerization of O ‐allyl acetals and O ‐allyl esters. The following allyl ethers, among the examined in this work, were isomerized in the presence of basis catalytic systems: 2 ( Q = t ‐BuO, t ‐BuOK), 3 (PhCH 2 , t ‐BuOK), 4 ( neo ‐menthyl O , LDA or t ‐BuOK), 6 (PhO, t ‐BuOK or LDA, or Vercade's super‐base,), 7 ( t ‐BuOK), 8 ( t ‐BuOK), and 9 ( t ‐BuOK). As mentioned above, the catalytic systems crown ether‐base type have not been applied to the O ‐allyl compounds isomerization so far.…”
Section: Resultsmentioning
confidence: 99%
“…As far as P ‐allyl systems are concerned, the isomerization of allyl diphenyl phosphine 27 is known from the literature, whereas the isomerization of diallyl phosphine 28 has not been described so far. Compound 27 was isomerized in the presence of 18‐Crown‐6/KOH in benzene, and NaOEt in EtOH . It was shown that the isomerization of various N ‐ and P ‐allyl and diallyl compounds could be effectively realized in mild conditions, using safe and easy to evaporate solvents and in short reaction time with the aid of the various type of base/crown ether systems selected appropriately to the N ‐ and P ‐allyl substrate reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphonate 3b was once synthesized by a rather tedious method because a simpler method through a base-catalyzed isomerization of dibenzyl 2-propenylphosphonate, the reaction originally reported for diethyl phosphonate, was unsuccessful . Among the other methods published, , the palladium-catalyzed reaction 16a of alkenyl halides and dialkyl phosphite (HP(O)(OR) 2 ) was investigated.…”
mentioning
confidence: 99%